Analysis of the Inventory Accounting System on Cv. Bangunan Jaya Sentosa - Lintong, Stevi; Amaliah, Tri Handayani; Wuryandini, Ayu Rakhma (Raudhah Publisher, 2025)
This study aims to analyze the inventory accounting system implemented at CV. Bangunan Jaya Sentosa and identify the challenges faced in inventory management. The research employs a qualitative approach with data collection techniques including interviews, observations, and documentation. The findings indicate that the inventory management system at CV. Bangunan Jaya Sentosa has not been effectively implemented. Warehouse recording processes lack thorough physical verification, resulting in discrepancies between physical stock and system records. Additionally, poor coordination between the warehouse, administration, and sales departments leads to inventory report inconsistencies, affecting the accuracy of the company's financial statements. CV. Bangunan Jaya Sentosa applies a perpetual recording system and uses the FIFO (First In, First Out) method for inventory valuation. However, warehouse records are still maintained manually, while the administration and sales departments use a computerized system. This imbalance causes recording errors and hampers inventory management efficiency. Therefore, it is recommended that the company integrate an accounting information system across departments to enable real-time inventory monitoring and improve data accuracy. Additionally, enhanced supervision and training for warehouse staff are necessary to minimize inventory recording errors. With an improved system and stricter internal controls, CV. Bangunan Jaya Sentosa can enhance operational efficiency and produce more accurate and reliable financial reports.